Influence of Sn doping ratio on the structural and optical properties of CdO films prepared by laser induced plasma - Aadim, Kadhim A.; Ahmed, Baida M.; Khalaf, Madyan A. (Iraqi Journal of Physics, 2020)
In this work, we study the effect of doping Sn on the structural and optical properties of pure cadmium oxide films at different concentrations of Tin (Sn) (X=0.1,0.3 and 0.5) .The films prepared by using the laser-induced plasma at wavelength of laser 1064 nm and duration 9 ns under pressure reached to 2.5×10-2 mbar. The results of X-ray diffraction tests showed that the all prepared films  are polycrystalline. As for the topography of the films surface, it was measured using AFM , where the results showed that the grain size increases with an increase in the percentage of doping  in addition to an increase in the average roughness. The optical properties of all films have also been studied through the absorbance spectrum of the range  of  the wavelength (350-1100) nm, where the optical energy gap was direct transitions it was found that the value of the optical energy gap increased with increasing the doping.